Geographical Alienation of Migrant Ranch Workers in John Steinbeck's Of Mice and Men - Adhikari, Agni; Gartaula, Sudeep; Neupane, Tika (KMC Research Journal, 2022)
Of Mice and Men, a novella of John Steinbeck tells the story of American migrant ranch workers. This article observes and analyzes the alienation of the migrant ranch workers in the novella Of Mice and Men in Depression-era America in relation to American geography. The issue revolves around the major characters: George Milton and Lennie Small, as well as other minor characters. The characters in the novella suffer from alienation caused by unfair geographical conditions resulting from the uneven distribution of means and resources. After all, the characters become the victim of mental retardation and they perform inhospitable behavior to one another. To explore this state of alienation and geography, this article applies library research and content analysis of the novella. To moor the issue, the Marxist theory of alienation has been applied that discusses the influence of class economy in human interaction. According to Marx, in the capitalist mode of production, a worker is alienated from the production process, nature, society, and hence finally, with himself. In the novella, alienation related to geography is depicted in subtle and clear forms that the characters feel disconnected from society and the surrounding environment and ultimately from their intimate ones. The theme of alienation and geography is depicted in the relationship the characters share, in the plot, which presents the movement of the major characters from ranch to ranch in pursuit of the American dream, and in the setting, which represents Weed, California, as the place of poverty and inequality during the depression era. The harsh geographical conditions, as depicted in the novella, contribute to the theme of alienation of the migrant ranch workers, who are surrounded by poverty even in the crowded setting.